Inclusive V0 production cross sections from 920 GeV fixed target proton-nucleus collisions: The HERA-B Collaboration - van Eldik, Christopher; et al. (European Physical Journal C, 2003)
Inclusive differential cross sections dσ/dx and dσ/dp for the production of K , Λ, and Λ̄ particles are measured at HERA in proton-induced reactions on C, Al, Ti, and W targets. The incident beam energy is 920 GeV, corresponding to √s = 41.6 GeV in the proton-nucleon system. The ratios of differential cross sections dσ(K )/dσ(Λ) and dσ(Λ̄)/dσ(Λ) are measured to be 6.2 ± 0.5 and 0.66 ± 0.07, respectively, for x ≈ -0.06. No significant dependence upon the target material is observed. Within errors, the slopes of the transverse momentum distributions dσ/dp also show no significant dependence upon the target material. The dependence of the extrapolated total cross sections σ on the atomic mass A of the target material is discussed, and the deduced cross sections per nucleon σ are compared with results obtained at other energies.